Cultural humility and working with marginalized populations in developing countries. (March 2015) - Kools, Susan; Chimwaza, Angela; Macha, Swebby
Population health needs in developing countries are great and countries are scaling up health professional education to meet these needs. Marginalized populations, in particular, are vulnerable to poor health and health care. This paper presents a culturally appropriate diversity training program delivered to Global Health Fellows who are educators and leaders in health professions in Malawi and Zambia. The purpose of this interprofessional education experience was to promote culturally competent and humble care for marginalized populations.